Kaj Munk’s “De Faldne” – Memorial Poem and Monument Inscription - Gemzøe, Anker (Scandinavistica Vilnensis, 2023)
On 29 August 1943, the Danish government resigned. The German Wehrmacht was to take immediate control of the Danish Army and Navy. Under widespread fighting against this “takeover,” 23 Danish soldiers and two civilians were killed, and a further 53 were wounded. Munk promptly wrote the poem “De Faldne” in memory of the soldiers killed in the assault on the Danish Army and Navy. In Munk’s wartime oeuvre, some dramas, poems and memoir work, implying a subtle, indirect appeal to resistance, have proved to be viable. His “direct” resistance poetry appears to be more time-bound. “De Faldne,” however, is a special case. It is one of his best “direct,” activist poems. As an inscription on memorials, it is sometimes referred to in ceremonial speeches, but it has remained untreated in the few serious recent readings of Munk’s resistance literature. It is therefore an aim of the present article to fill in a gap. When Munk wrote this memorial poem, he had already – through the open, resolute will to confront the occupiers which he had advocated at every possible occasion after 9 April 1940 – achieved a unique status as a national resistance icon. This status was further cemented when he himself joined the ranks of “De Faldne.” During the night of 4 January 1944, he was arrested and killed. His funeral became a national event, and the brutal murder indeed strengthened rather than weakened the will to resistance. “De Faldne” began to exert a strong and lasting influence on the construction of the collective memory of World War II and the Occupation when, after the Liberation, the first stanza was carved as an inscription in two places at the central memorial site for those killed in the freedom struggle, Mindelunden in Ryvangen. This first stanza was moreover used on a considerable number of memorial stones erected on local initiative throughout the country. The present article offers an analysis of its important role in the memory culture of the Occupation, both through its concrete presence on numerous monuments and as part of a wider memorial culture with ceremonial anniversaries and commemoration days like 9 April (the Occupation, 1940), 4–5 May (the Liberation, 1945), and 29 August (the end of the politics of cooperation, 1943). This commemorative culture has retained its public appeal, perhaps even growing more important in recent years due to the shift toward a more activist Danish foreign policy since the 1990s. Quite recently, several of the monuments with Munk’s words as an inscription have been revitalised and enhanced by musical and visual dimensions transmitted by new, digital forms of communication. Through the modification of this cultural heritage, Munk’s words, as well as his fate, have become audible and visible in new ways.